Teaching materials for ESL distance learning - Memić-Fišić, Iris; Bijedić, Nina (ExELL, 2025)
Distance education, as a form of education that enables and promotes development of autono-mous life-long learning skill, necessary to keep up with rapid changes and development in today’s society, is a concept definitely worth considering. Teaching a foreign language in a distance education system is very challenging, primarily in terms of overcoming the main gap – lack of direct contact between teachers and learners. This paper focuses on the aspect of teaching materials used for ESL in a distance learning system.